Ethical receptive capacity and teaching business ethics. (1st January 2012) - Tangpong, Chanchai; Michalisin, Michael D.; Li, Jin
In this study, we proposed the ethical receptive capacity (ERC) perspective on teaching business ethics. The ERC perspective was developed on two premises: the separation of personal moral values and professional ethics, and the path dependent nature of professional ethics, such that individuals in the early stage of their profession have higher ERC (i.e., individuals' capacity to receive ethical contents) and thus are more receptive to new ethical contents prescribed to them. The experimental results in this study supported the ERC perspective, suggesting that business ethics education should be introduced to students as early as possible in their business programme.